Booked ebook - Alexander, Kwame (Crossover Graphic Novel, 2022)
In this electrifying follow-up to Kwame Alexander's Newbery winner The Crossover, soccer, family, love, and friendship take center stage. A New York Times bestseller and National Book Award Longlist nominee, now in a graphic novel edition featuring art from Dawud Anyabwile. Twelve-year-old Nick learns the power of words as he wrestles with problems at home, stands up to a bully, and tries to impress the girl of his dreams. Helping him along are his best friend and sometimes teammate Coby, and The Mac, a rapping librarian who gives Nick inspiring books to read. This electric and heartfelt novel-in-verse bends and breaks as it captures all the thrills and setbacks, action and emotion of a World Cup match. "A novel about a soccer-obsessed tween boy written entirely in verse? In a word, yes. Kwame Alexander has the magic to pull off this unlikely feat, both as a poet and as a storyteller. " —The Chicago Tribune Can't nobody stop you Can't nobody cop you...